A chemometric approach to source apportionment, ecological and health risk assessment of heavy metals in industrial soils from southwestern Nigeria. Issue 14 (14th November 2022) - Egbueri, Johnbosco C.; Ukah, Bernadette U.; Ubido, Oyem E.; Unigwe, Chinanu O.
ABSTRACT: In recent times, heavy metal pollution in soils has become a serious threat to many communities in the developing countries due to rapid urbanisation and industrialisation, thereby exposing different populations to adverse ecological and health risks. The purpose of this study was to assess the pollution status, pollution sources, ecological and human health risks of heavy metals in industrial soils from the densely populated Ajao area, southwestern Nigeria. Several numerical models revealed low extent of heavy metal pollution in the industrial soils. Chemometric analysis identified anthropogenic inputs as the major sources of pollution in the soils. Ecological risk index showed that all the analysed heavy metals pose low ecological risks. Daily exposure assessment for ingestion, dermal contact and inhalation showed that children are more exposed than the adult population. Hazard index revealed that most of the samples pose low-high chronic risks due to ingestion by adults. However, all the samples were observed to pose medium-high chronic health risks due to ingestion by children. Except Cd, all the carcinogens pose negligible cancer risk due to ingestion by the adult population; but Ni, Cr and Cd pose significant cancer risk to children. Furthermore, Ni and Cd tend to pose high lifetime cancer risk (LCR) to adults. However, Ni, Cr and Cd pose high LCR to the children population. Therefore, emphasis should be placed on Ni, Cr and Cd in any attempt to halt or mitigate further heavy metal pollution in the study area.